2005
DOI: 10.1002/pon.839
|View full text |Cite
|
Sign up to set email alerts
|

The course of life of survivors of childhood cancer

Abstract: The developmental consequences in adulthood of growing up with childhood cancer are not well understood. The Course of life questionnaire was developed to assess the attainment of developmental milestones retrospectively and socio-demographic outcomes in young adulthood. The aim of this study was to assess the course of life and socio-demographic outcomes in young adult survivors of childhood cancer. Knowledge about possible gaps in the course of life could enable health care providers to aim for the most favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
251
3
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(275 citation statements)
references
References 23 publications
13
251
3
8
Order By: Relevance
“…First, the items are based on the literature and clinical experience. Second, the results among a normative population of 508 young adults from the general Dutch population proved to be in line with several datasets of the Dutch population [11,12]. The test-retest reliability is good (r≥0.86) [13].…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…First, the items are based on the literature and clinical experience. Second, the results among a normative population of 508 young adults from the general Dutch population proved to be in line with several datasets of the Dutch population [11,12]. The test-retest reliability is good (r≥0.86) [13].…”
Section: Methodssupporting
confidence: 64%
“…This Dutch instrument was developed by the Psychosocial Department of the Emma Children's Hospital/Academic Medical Centre in order to be able to investigate the course of life of young adults, aged 18-30 years, who have grown up with a chronic or lifethreatening disease, and to facilitate comparison with the course of life of peers without a history of disease [11]. Reference values were obtained from 508 young adults, aged 18-30 years, from the general population [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the reliability of the social functioning scale of the TACQOL was moderate. This is a very interesting domain in our opinion, because recent research revealed that the social development of young adult long-term survivors of childhood cancer was hampered [31].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why survivors report a preference for interacting with others [31] and more positive emotions when interacting with others [31] than comparison groups. Trying to fit in with their former social life, survivors may be eager to present themselves favourably [42], and may exhibit less antisocial [63], aggressive and disruptive behaviour [65] than comparison groups. However, most results with regard to friendship demonstrate poorer function regarding friendship [41] as well as lower satisfaction regarding friendship [31] for survivors as compared to comparison groups.…”
Section: Discussionmentioning
confidence: 99%
“…See Table III for a presentation of results in studies with a comparative design with regard to this theme. A more positive attitude towards the family [43], a preference for interacting with others [31], more positive emotions when interacting with others [31], better social relationships [43], and less anti-social behaviour [63] than for comparison groups were expressed by self-reports. Teachers reported less aggressive and disruptive behaviour for survivors than for a comparison group [65].…”
Section: Relations To Othersmentioning
confidence: 99%